2015
DOI: 10.1121/1.4916706
|View full text |Cite
|
Sign up to set email alerts
|

The equivalent translational compliance of steel or wood studs and resilient channel bars

Abstract: A number of recent papers have determined the compliance of steel studs for use in models for predicting the sound insulation of cavity stud walls. However, in these papers, the compliance of resilient channel bars on one or both sides of wood studs or on one side of steel studs has not been determined across the whole of the frequency range. The present paper determines the compliance of the combination of resilient channel bars, mounted on wooden or steel studs and modeled as point or as line connections. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The Rw-frequency curve of the W2 specimen revealed a declining trend at 3150 Hz due to a coincidence effect at high-frequency bands caused by the incident acoustic wave being in the same phase when superimposed. As the bending wave propagates upwards, the vibration becomes more intense with distance, resulting in a sound isolation trough at high-frequency (Hirakawa and Davy, 2015;Mao et al, 2014;Reynolds, 1984). Lin et al (2021) found the same resonance and coincidence dips of the CLT wall system in Rw-frequency curves as this study, indicating that wood is generally considered as disadvantage compared with other building element regarding airborne sound insulation.…”
Section: Figure 5 Near Heresupporting
confidence: 75%
“…The Rw-frequency curve of the W2 specimen revealed a declining trend at 3150 Hz due to a coincidence effect at high-frequency bands caused by the incident acoustic wave being in the same phase when superimposed. As the bending wave propagates upwards, the vibration becomes more intense with distance, resulting in a sound isolation trough at high-frequency (Hirakawa and Davy, 2015;Mao et al, 2014;Reynolds, 1984). Lin et al (2021) found the same resonance and coincidence dips of the CLT wall system in Rw-frequency curves as this study, indicating that wood is generally considered as disadvantage compared with other building element regarding airborne sound insulation.…”
Section: Figure 5 Near Heresupporting
confidence: 75%
“…The equivalent translational compliance of a steel stud frame and the method that fastens the wall leaves to the steel stud frame is the compliance of translational line springs spaced at the stud spacing distance for the line connection model, or the compliance of translational point springs for the point connection model, which transfer the same amount of vibrational power between the two wall leaves as the steel stud frame and the method that fastens the wall leaves to the steel stud The empirical equations for the equivalent translational compliance CM are A is a constant, f is the frequency, f0 is 1 Hz, mr is the reduced surface density, mr0 is 1 kg/m 2 , b is the distance between the line connections (stud spacing), b0 is 1 m, n is the number of point connections per unit area calculated from the stud spacing and the screw spacing, n0 is 1 1/m 2 , g is the gauge of the sheet steel used to manufacture the steel studs, g0 is 1, S is the area of the wall and S0 is 1 m 2 . The constant A has units of 1/Pa for line connections and m/N for point by Davy et al (2018) with that derived by Hirakawa and Davy (2015). There is rough agreement between these compliances derived by different authors.…”
Section: Studsmentioning
confidence: 77%
“…The point compliance of nominal 25 gauge steel studs, with gypsum plaster board leaves with a reduced surface density of 4.9 kg/m 2 , with 5.4 point connections per square metre and a specimen area of 7.4 m 2 derived by Davy et al (2018) with that derived by Hirakawa and Davy (2015).…”
Section: Fig 2 (Color Online)mentioning
confidence: 90%
See 1 more Smart Citation
“…As explained in detail by Davy, 61 this happens because it is possible for total internal reflection to occur for vibration incident at a non-normal angle to a line connection. More recently, Hirakawa and Davy 64 have obtained empirical formulae for the translational compliance of resilient channel bars and of thicker gauge steel studs. Vigran 65 developed a modified decoupled approach within the transfer matrix method (TMM), which allows to take into account the structure-borne sound transmission due to point and line connections.…”
Section: Double-leaf Partitionsmentioning
confidence: 99%